Health Risks in Disaster Responders: A Conceptual Framework. Issue 2 (3rd May 2019) - Khatri, Jyoti; Fitzgerald, Gerard; Poudyal Chhetri, Meen B.
Abstract : Introduction: Disasters cause severe disruption to socio-economic, infrastructural, and environmental aspects of community and nation. While the impact of disasters is strongly felt by those directly affected, they also have significant impacts on the mental and physical health of relief/recovery workers and volunteers. Variations in the nature and scale of disasters necessitate different approaches to risk management and hazard reduction during the response and recovery phases. Method: Published articles (2010-2017) on the quantitative and quantitative relationship between disasters and the physical and mental health of relief/recovery workers and volunteers were systematically collected and reviewed. A total of 162 relevant studies were identified. Physical injuries and mental health impacts were categorized into immediate, short-term, and chronic conditions. A systematic review of the literature was undertaken to explore the health risks and injuries encountered by disaster relief workers and volunteers, and to identify the factors contributing to these and relating mitigation strategies. Results: There were relatively few studies into this issue. However, the majority of the scrutinized articles highlighted the dependence of nature and scope of injuries with the disaster type and the types of responders, while the living and working environment and socio-economic standing also had significant influence on health outcomes. Conclusion: A conceptual framework derived from the literature review clearly illustrated several critical elements that directly or indirectly cause damage to physical and mental health of disaster responders. Pre-disaster and post-disaster risk mitigation approaches may be employed to reduce the vulnerability of both volunteers and workers while understanding the identified stressors and their relationships. Khatri KC J, Fitzgerald G, Poudyal Chhetri MB. Health risks in disaster responders: a conceptual framework. Prehosp Disaster Med . 2019;34(2):209–216